2020
DOI: 10.1002/hbm.25283
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of neural oscillations during working memory update, maintenance, and readout: An hdEEG study

Abstract: Working memory (WM) performance is very often measured using the n‐back task, in which the participant is presented with a sequence of stimuli, and required to indicate whether the current stimulus matches the one presented n steps earlier. In this study, we used high‐density electroencephalography (hdEEG) coupled to source localization to obtain information on spatial distribution and temporal dynamics of neural oscillations associated with WM update, maintenance and readout. Specifically, we a priori selecte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…2005; Raghavachari et al, 2006;Semprini et al, 2020;Yu et al, 2020). Studies of human EEG have shown that increased theta activity is associated with item encoding in working memory (Jensen and Tesche, 2002;Proskovec et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…2005; Raghavachari et al, 2006;Semprini et al, 2020;Yu et al, 2020). Studies of human EEG have shown that increased theta activity is associated with item encoding in working memory (Jensen and Tesche, 2002;Proskovec et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A larger number of previous studies revealed that, compared with happy and neutral faces, angry faces significantly improved the working memory capacity for facial identity (111)(112)(113)(114)(115), and the working memory sensitivity for fearful faces was higher than that for neutral faces (116). Working memory is an ability that preserves and updates information in a short period of time (117)(118)(119). The stronger working memory processing on negative emotional faces among adolescent delinquents may imply difficulty in refreshing negative information, and thus cause aggressive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…During the “retention” or “maintenance” intervals of WM tasks, frontal gamma synchronization may be a relatively specific marker of prefrontal gamma activity. In support of this model, Semprini and colleagues demonstrated that the maintenance phase of the N-Back (a WM task) was associated with significant gamma synchronization, especially in frontal, and dorsal-lateral prefrontal (DLPFC) areas [ 27 ]; in contrast, gamma activity during the encoding and retrieval phases were relatively attenuated (with theta and beta activity being more prominent). Tallon-Baudry and colleagues similarly demonstrated significant frontal (e.g., F3, F4) gamma synchronization during the maintenance interval of a visual WM task (delayed match to sample, or DMS), compared to control intervals where maintenance were not required [ 21 ].…”
Section: Neural Basis Of Working Memory and Other Cognitive Functionsmentioning
confidence: 99%